Hubungan Antara Konsep Diri dengan Efikasi Diri dalam Memecahkan Masalah melalui Konseling Individu di SMK Hidayah Semarang - Dewi, Yolanda Puspita; Mugiarso, Heru (Konseling Edukasi : Journal of Guidance and Counseling, 2020)
The Relationship Between Self Concept and Self Efficacy in Solving Problems through Individual Counseling at Hidayah Vocational School Semarang. This study aims to determine the relationship between self-concept and self-efficacy in solving problems through individual counseling at SMK Hidayah Semarang. This research is a type of correlational quantitative research. Sampling using purposive sampling and simple random sampling. The sample in the study consisted of 83 students who were spread across all classes at SMK Hidayah Semarang. The measuring instrument used is the self-concept scale and the self-efficacy scale in solving problems. Data analysis used in hypothesis testing is a simple correlation test. The results showed that self-efficacy in solving problems was classified as high and had a positive and significant relationship between these variables. The results obtained a correlation of 0.580 with a significance of 0.000 or <0.05. From these results it can be understood that the higher the student's self-concept, the higher the self-efficacy in solving student problems. With this research it is useful for guidance and counseling teachers to provide innovation when conducting individual counseling services.Keywords: self-concept, self-efficacy, individual counseling